Clustering Pemetaan Tingkat Kemiskinan di Provinsi Jawa Barat Menggunakan Algoritma K-Means - I Wayan Setya Adi Nugraha (Peneliti.net, 2023)
One of the problems Indonesia is still facing is the problem of poverty. The issue of poverty is complex and multifaceted in society and has become a government development priority. The percentage of poverty in Indonesia at the beginning of the pandemic in March increased by 9.78% and in September it increased by 10.19%. West Java ranks first in the highest level of extreme poverty in Indonesia with a total of 17,856 cases, reported on radarsukabumi.com. This study uses the clustering method with the k-means algorithm and mapping poverty-prone areas using QGIS. The results of grouping poverty-prone areas in West Java Province in 2015 to 2020 found 12 districts/cities not vulnerable, 14 districts/cities prone and 1 district/city very vulnerable. The results of the clustering evaluation using the silhouette coefficient that is equal to 0.55. The evaluation results fall into the category of medium structure with a reasonable interpretation of cluster placement.